Az alkotmánybíráskodás elméleti alapjairól - Szmodis, Jenő (Debreceni Jogi Műhely, 2015)
The paper researches preliminarily the problem of norm-control versus social-control. It criticizes the logical and normative approach of Consctitutional Court’s activity, pointing out this function necessarily deals with values. The paper introduces the ideological and historical antecedents of modern institutional norm-control, touching Grecian and early American ideas. The article finally refers spread of Constitutional Courts and some problematical phenomena of Hungarian Constitutional Court's activity.